2015
DOI: 10.1016/j.canlet.2015.07.038
|View full text |Cite
|
Sign up to set email alerts
|

High affinity and covalent-binding microtubule stabilizing agents show activity in chemotherapy-resistant acute myeloid leukemia cells

Abstract: Treatment failure in acute myeloid leukemia (AML) is frequently due to the persistence of a cell population resistant to chemotherapy through different mechanisms, in which drug efflux via ATP-binding cassette (ABC) proteins, specifically P-glycoprotein, is one of the most recognized. However, disappointing results from clinical trials employing inhibitors for these transporters have demonstrated the need to adopt different strategies. We hypothesized that microtubule targeting compounds presenting high affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…45, 46 To investigate whether alectinib could reverse ABCB1-mediated MDR in ex vivo , bone marrow samples were collected from resistant patients with AML or CML. Four of the eleven patient samples exhibited high expression of ABCB1 (Figure 7a).…”
Section: Resultsmentioning
confidence: 99%
“…45, 46 To investigate whether alectinib could reverse ABCB1-mediated MDR in ex vivo , bone marrow samples were collected from resistant patients with AML or CML. Four of the eleven patient samples exhibited high expression of ABCB1 (Figure 7a).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the ABCB1 is expressed in AML/CML patients [24]. We obtained the bone marrow samples from AML/CML patients according to the FAB classification after getting their informed consent, and this study was approved by the Ethics Review Committee at Sun Yat-Sen University Cancer Center.…”
Section: Methodsmentioning
confidence: 99%
“…IL-3 and KL and Epo were obtained from R and D Systems (Minneapolis, USA) and G-CSF was from Amgen (Thousand Oaks, CA). Colonies were scored 14 days after plating as per the protocol described earlier [42]. …”
Section: Methodsmentioning
confidence: 99%